Study of the reflectance distributions of fluoropolymers and other rough surfaces with interest to scintillation detectors - Silva, Cláudio Frederico Pascoal da (2010)
Tese de doutoramento em Física (Física Experimental), apresentada à Faculdade de Ciências e Tecnologia da Universidade de Coimbra